2020
DOI: 10.3390/rs12111845
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Walker Constellation Design of LEO-Based Global Navigation and Augmentation System

Abstract: Low Earth orbit (LEO) satellites located at altitudes of 500 km~1500 km can carry much stronger signals and move faster than medium Earth orbit (MEO) satellites at about a 20,000 km altitude. Taking advantage of these features, LEO satellites promise to make contributions to navigation and positioning where global navigation satellite system (GNSS) signals are blocked as well as the rapid convergence of precise point positioning (PPP). In this paper, LEO-based optimal global navigation and augmentation constel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Supposing the reference satellite's RAAN is RAAN o [ • ] and its mean anomaly (MA) -the position of satellites on each orbit plane-is MA o [ • ]. Following the WC method, as shown in Figure A1 (right), RAAN i [ • ]-the RAAN of the i-th orbit-and MA i,j [ • ]-the MA of the j-th satellite on the i-th orbit-can be calculated as follows [24]:…”
Section: Discussionmentioning
confidence: 99%
“…Supposing the reference satellite's RAAN is RAAN o [ • ] and its mean anomaly (MA) -the position of satellites on each orbit plane-is MA o [ • ]. Following the WC method, as shown in Figure A1 (right), RAAN i [ • ]-the RAAN of the i-th orbit-and MA i,j [ • ]-the MA of the j-th satellite on the i-th orbit-can be calculated as follows [24]:…”
Section: Discussionmentioning
confidence: 99%
“…In [13], a Genetic Algorithm (GA)-based optimization, with Geometric Dilution of Precision (GDOP) and the number of satellites as optimization metrics, was employed for space-segment optimization of a LEO-based navigation system relying on a Walker constellation. It was found that good LEO coverage for navigation purposes can be reached with constellations between 180 and 264 and satellites placed at orbital altitudes between 900 and 1500 km.…”
Section: Related Workmentioning
confidence: 99%
“…With regards to the space segment, an objective function can simply be any of the already mentioned metrics (i.e., C/N 0 for GNSS or LEO-PNT applications as well as for high communication throughputs), some combination of them (i.e., C/N 0 and GDOP), or completely custom crafted as in [20,74]. As an example, we present Equation (13), which defines an objective function f (x) that combines the C/N 0 and the launch cost C launch using some weights w 1 and w 2 , where x is the vector of the required parameters for the calculations. Note that in a typical ML-based method, these weights are fine-tuned by the optimization process, but they can also be tuned manually, which is typical for evolutionary algorithms.…”
Section: Optimization Metrics Related To the Space Segmentmentioning
confidence: 99%
“…Both GNSS and LEO constellation simulations in this paper are Walker constellations and aim to optimize constellation coverage with a given number of satellites. Walker constellation is proposed after Ballard's improvement in literature [31], forming a constellation system widely used in the field of orbit design [32].…”
Section: Gnss and Leo Constellation Simulationmentioning
confidence: 99%